Mispronouncing of Consonant Alveolar Plosive /t/, and /d/ in The Final position in English byTarakanese - Fithrah Auliya Ansar; arwissyahIrwan Duhir (International Journal of Science, Technology & Management, 2020)
This study aims to examine whether speakers who have a basic English language make mistakes in pronouncing the plosive / t /, / d / consonants due to the influence of the Tarakan language, which is the language of the speakers during their domicile in the area. A recording technique was used in collecting data. The instrument used is a list of words, sentences and paragraphs. The population in this study were English-bachelor students who had lived in Tarakan for a long time and were accustomed to using the Tarakan accent. The sampling technique used was purposive sample of 3 people. Data were analyzed using descriptive qualitative methods by analyzing the data of the transcription.The results of this study indicate that in pronouncing English consonants and vowels, there are still many students who do not pronounce them correctly. They make a lot of mistakes in pronouncing the plosive / d / correctly in every word. They tend to change it to / t /.